Impact of aerosol in-situ peroxide formations induced by metal complexes on atmospheric H2O2 budgets - Song, Huan; Lu, Keding; HuaBin Dong; Zhaofeng Tan; Shiyi Chen; Zhongming Chen; Limin Zeng; Yuanhang Zhang (Science of The Total Environment, 2023)
Hydrogen peroxide (H2O2), hydroxyl radicals (OH), hydroperoxyl (HO2), and superoxide (O2−) radicals interacting with aerosol particles significantly affect the atmospheric pollutant budgets. A multiphase chemical kinetic box model (PKU-MARK), including the multiphase processes of transition metal ions (TMI) and their organic complexes (TMI-OrC), was built to numerically drive H2O2 chemical behaviors in the aerosol particle liquid phase using observational data obtained from a field campaign in rural China. Instead of relying on fixed uptake coefficient values, a thorough simulation of multiphase H2O2 chemistry was performed. In the aerosol liquid phase, light-driven TMI-OrC reactions promote OH, HO2/O2−, and H2O2 recycling and spontaneous regenerations. The in-situ generated aerosol H2O2 would offset gas-phase H2O2 molecular transfer into the aerosol bulk phase and promote the gas-phase level. When combined with the multiphase loss and in-situ aerosol generation involving TMI-OrC mechanism, the HULIS-Mode significantly improves the consistency between modeled and measured gas-phase H2O2 levels. Aerosol liquid phase could be a pivotal potential source of aqueous H2O2 and influence the multiphase budgets. Our work highlights the intricate and significant effects of aerosol TMI and TMI-OrC interactions on the multiphase partitioning of H2O2 when assessing atmospheric oxidant capacity.
Keywords: HO; Multiphase chemistry kinetic model; radicals; TMI and organic complexes